2020
DOI: 10.1093/cid/ciaa929
|View full text |Cite
|
Sign up to set email alerts
|

Integration of FDG-PET/CT in the Diagnostic Workup for Staphylococcus aureus Bacteremia: A Prospective Interventional Matched-cohort Study

Abstract: Abstract Background Staphylococcus aureus bacteremia (SAB) is uniquely characterized by focal pyogenic complications that might not be apparent clinically. We investigated the benefit of adding FDG-PET/CT in the workup of patients with SAB. Methods Matched-cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Earlier studies have shown that up to 71% of metastatic foci are clinically silent [8], leading to an underestimation of the bacterial burden in SAB patients. 2-[ 18 F]fluoro-2-deoxy-D-glucose positron emission tomography with combined computed tomography ([ 18 F]FDG-PET/CT) has a high sensitivity and specificity for metastatic infectious foci [9,10]. Integration of [ 18 F]FDG-PET/CT into the diagnostic workup of patients with SAB reduces mortality rates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that up to 71% of metastatic foci are clinically silent [8], leading to an underestimation of the bacterial burden in SAB patients. 2-[ 18 F]fluoro-2-deoxy-D-glucose positron emission tomography with combined computed tomography ([ 18 F]FDG-PET/CT) has a high sensitivity and specificity for metastatic infectious foci [9,10]. Integration of [ 18 F]FDG-PET/CT into the diagnostic workup of patients with SAB reduces mortality rates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2-[ 18 F]fluoro-2-deoxy-D-glucose positron emission tomography with combined computed tomography ([ 18 F]FDG-PET/CT) has a high sensitivity and specificity for metastatic infectious foci [9,10]. Integration of [ 18 F]FDG-PET/CT into the diagnostic workup of patients with SAB reduces mortality rates [8][9][10]. Proof of concept studies indicate that [ 18 F]FDG-PET/CT can also be used to select patients who are eligible for iv-oral switch [11] or shortening of antibiotic treatment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although none of the cases reported in the literature used FDG-PET/CT for therapy decision-making, it is possible that if used as an auxiliary follow-up tool it can facilitate decisions on treatment duration [50]. Similarly, FDG-PET/CT conducted shortly after the diagnosis of Staphylococcus aureus bacteremia guided treatment duration and improved survival [3]. Furthermore, FDG-PET/CT facilitated monitoring of the initial response to antibiotic therapy in infectious spondylodiscitis [51] and in predicting relapse of pulmonary tuberculosis when conducted at the time of treatment completion [52].…”
Section: Discussionmentioning
confidence: 99%
“…Integrated positron emission tomography/computed tomography (PET/CT) with 18-fluorodeoxyglucose (FDG) is a useful modality for managing some infections [1], mostly disseminated infections [2,3]. FDG-PET/ CT can predict extracardiac infective endocarditis (IE) complications [4], and contributes to its treatment approach and decision-making [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we present and review contemporary studies of SAB across a range of topics not limited to epidemiology, clinical features, multiple positive blood cultures, antibiotic choice and duration. SAB is complex and there are many important aspects that we were not able to explore further at this time including a study with eosinophilia with daptomycin [40], use of oral stepdown therapy with clindamycin [41], improvement of diagnosis using fluorodeoxyglucose positron emission tomography/ computed tomography (FDG-PET/CT) [42,43], source control such as with removal of cardiac implantable electronic devices associated with decreased mortality [44], the importance of serial negative blood cultures [45 & ], and the significance of Staphylococcus aureus bacteriuria in patients with SAB [46 & ]. In addition, optimized use of clinical scoring systems to stratify patients for therapy or best utilize echocardiography resources is a major area of investigation that could merit its own review [47][48][49][50][51][52][53][54].…”
Section: Closing Remarksmentioning
confidence: 99%